A Potent Histone Deacetylase Inhibitor MPT0E028 Mitigates Emphysema Severity via Components of the Hippo Signaling Pathway in an Emphysematous Mouse Model - Yeh, Lu-Yang; Fang, Yu-Ting; Lee, Hong-Sheng; Liu, Chia-Hao; Chen, You-Yin; Lo, Yu-Chun; Laiman, Vincent; Liou, Jing-Ping; Chung, Kian Fan; Chuang, Hsiao-Chi; Lin, Chien-Huang (Frontiers in Medicine, 2022)
Background Chronic obstructive pulmonary disease (COPD) is a major cause of chronic mortality. The objective of this study was to investigate the therapeutic potential of a novel potent histone deacetylase (HDAC) inhibitor MPT0E028 on emphysema. Materials and Methods A mouse model of porcine pancreatic elastase (PPE)-induced emphysema was orally administered 0, 25, or 50 mg/kg body weight (BW) of the MPT0E028 five times/week for 3 weeks. Pulmonary function, mean linear intercept (MLI), chest CT, inflammation, yes-associated protein (YAP), transcriptional coactivator with PDZ-binding motif (TAZ), surfactant protein C (SPC), T1-α, p53, and sirtuin 1 (SIRT1) levels were examined. Results 50 mg/kg BW of the MPT0E028 significantly decreased the tidal volume in emphysematous mice (p < 0.05). Emphysema severity was significantly reduced from 26.65% (PPE only) to 13.83% (50 mg/kg BW of the MPT0E028). Total cell counts, neutrophils, lymphocytes, and eosinophils significantly decreased with both 25 and 50 mg/kg BW of the MPT0E028 (p < 0.05). Also, 50 mg/kg BW of the MPT0E028 significantly decreased the levels of KC, TNF-α, and IL-6 in lung tissues and serum (p < 0.05). Expressions of p-TAZ/TAZ in lung tissues significantly decreased with 50 mg/kg BW of the MPT0E028 (p < 0.05). Expressions of p53 significantly decreased in alveolar regions with 50 mg/kg BW of the MPT0E028 (p < 0.05), and the expression of SPC increased in alveolar regions with 50 mg/kg BW of the MPT0E028 (p < 0.05). Conclusions Our study showed that the potent HDAC inhibitor MPT0E028 reduced the severity and inflammation of emphysema with improvement in lung function, which could be regulated by Hippo signaling pathway. The MPT0E028 may have therapeutic potential for emphysema.